Pengembangan Buku Ajar Profesi Keguruan Berbasis Isu-Isu Pendidikan Terkini - Widodo, Ganjar Setyo; Hidayah, Layli (JU-ke: Jurnal Ketahanan Pangan, 2018)
The development of Teacher Professional Policies that are constantly changing, of course, prospective teachers must get the latest scientific knowledge. This study aims at making a product of textbook of Teaching Profession Based Current Educational Issues . The researcher used the development research steps adapted from the ADDIE model (Analysis-Design-Develop-Implement-Evaluate). The results of this study are 80.31% of students stating that the product is very useful, understandable, and easy to use.